Toward Sustainable Rainbow Trout Lipid Nutrition: A Systematic Review of Lipid Optimization Strategies in Controlled Conditions - Rosendo L. Azcuy; Alejandro Villasante; Susana Perelman; Matías E. Casaretto; Patricio Dantagnan; Gabriel A. Morales; Stefanie Colombo (Reviews in Aquaculture, 2026)
Replacing fish oil (FO) in feeds remains a challenge for aquaculture sustainability. While experimental studies have evaluated the effects of alternative lipids on fillet long‐chain polyunsaturated fatty acids (LC‐PUFA) in rainbow trout, a quantitative synthesis of these effects is lacking. Here, 119 experimental diets from 29 controlled studies were synthesized through a statistical framework combining linear mixed‐effects models (LMM), generalized additive models (GAM), and leave‐one‐study‐out validation. Dietary docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) consistently predicted fillet DHA and EPA concentrations, independent of growth rate and not significantly influenced by temperature or lipid level. While growth performance was unaffected by FO replacement, LC‐PUFA deposition was not equivalent across lipid origins: FO and vegetable‐based diets supported steeper diet‐to‐fillet transfer slopes compared to animal‐derived lipids. GAMs revealed non‐linear thresholds, with active deposition occurring only when dietary LC‐PUFA exceeded near 10 mg g −1 and the dietary n‐6:n‐3 ratio remained below approximately 4. Temperature, modelled linearly, showed no significant effect on fillet LC‐PUFA deposition within the analysed dataset. These results demonstrate that FO can be reduced without compromising growth, but not without reformulating LC‐PUFA supply and precursor balance. Successful FO replacement is therefore a formulation problem rather than an ingredient substitution issue. Emerging sources such as algal oils or engineered oilseeds represent a viable pathway toward sustainable feeds delivering nutritionally valuable fillets. The identified dietary thresholds provide practical guidance for feed formulation by defining minimum LC‐PUFA inclusion levels and n‐6:n‐3 ratios required to achieve target fillet EPA and DHA concentrations under controlled temperature conditions.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

P18-36 “Cross-species” Liver Microtissues: Species-specific microphysiological test systems for comparative toxicological in vitro studies during nonclinical drug safety assessment - M.V. Colombo; F. Wenz; L. Fäs; A. Pawlowska; A. Wolf; B.G. Filippi (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

P12-05 Species-specific liver microtissues: a set of micro-physiological systems to study translational hepatotoxicity in safety assessment - M.V. Colombo; F. Wenz; L. Fäs; A. Borgström; A. Wolf; B.G.H. Filippi (Toxicology Letters, 2024)

When another one bites the dust: Environmental impact of global copper demand on local communities in the Atacama mining hotspot as registered by tree rings - Nicolás C. Zanetta-Colombo; Tobias Scharnweber; Duncan A. Christie; Carlos A. Manzano; Mario Blersch; Eugenia M. Gayo; Ariel A. Muñoz; Zoë L. Fleming; Marcus Nüsser (Science of The Total Environment, 2024)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

The impact of Li-bearing pegmatite mining on the dissolved geochemical signature of a mountain stream in the Pampean ranges, Central Argentina - Milagros Marqués; Andrea I. Pasquini; María Gabriela García; Verena A. Campodonico; Fernando Colombo; Diego M. Gaiero; Karina L. Lecomte (Sustainable Water Resources Management, 2023)

Study of the mechanical properties of thermoplastic polyurethane (TPU) recycled from end-of-life ski-boots and techno-economic analysis (TEA) of the mechanical recycling processes - A. Nanni; L. Crosetta; G. La Fauci; F. Biagi; M. Parisi; D. Colombo; M. Colonna (Sustainable Chemistry and Pharmacy, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Sandstone petrofacies, deformational events and the dynamic of the Valle Fértil Lineament during the late Paleozoic (Paganzo Basin, northwestern Argentina) - Luis A. Spalletti; Carlos O. Limarino; Ferrán Colombo; Patricia L. Ciccioli; Carina E. Colombi (Journal of South American Earth Sciences, 2023)

Who let the young‐of‐the‐year ( YOY) up? The pelagic habitat as a nursery and feeding ground area for the YOY Argentine hake Merluccius hubbsi Marini, 1933 - Mauro Belleggia; Gustavo L. Alvarez‐Colombo; Betina A. Santos; Martin Castelletta; Belen Mattera (Journal of Fish Biology, 2022)
The young‐of‐the‐year (YOY) Argentina hake Merluccius hubbsi remained at particular distances off the seabed at pelagic habitat, in a nursery area located in the San Jorge Gulf off south‐western Atlantic. Older specimens were daylight distributed near the bottom in the demersal habitat. In this paper the authors show that the pelagic habitat is favourable for YOY hake compared to the surrounding demersal habitat by decreasing the probability of encounter with larger hake protecting the YOY against conspecific predation, and providing a better food supply. From 303 stomachs of pelagic YOY Argentine hake analysed (60–250 mm), 274 (90.43%) contained prey. Pelagic Argentine YOY hake fed almost exclusively on zooplanktonic crustaceans ( Euphausia spp. and Themisto gaudichaudii ). From 980 demersal specimens (14–82 cm), 572 (58.36%) contained prey, mainly the lobster krill Munida gregaria , followed by other hakes by cannibalism. The intensity of feeding was higher on pelagic layers. The allometric weight–length relationship revealed that the YOY Argentine hake find sufficient food in the pelagic habitat to live and develop, by increasing their relative body thickness. The cannibalism increases from close to zero when the YOY hake are c . 20 m off the seabed, to between 15% (cold season) and 20% (warm season) when they are 10 m off the seabed. These results suggest that the pelagic habitat is a feeding ground for YOY hake, and it is a favourable one compared to the surrounding demersal habitat by protecting the YOY from cannibalism. Pelagic YOY hakes were less abundant and more distant from the bottom during the cold season (14.3 m) than during warm one (11.4 m), probably because of natural mortality and progressive recruitment to demersal habits.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Pumice clasts in cross stratified basalt-dominated sandstones and conglomerates. Characteristics and depositional significance: Huarenchenque Fm (Neuquén, Argentina) - F. Colombo; R. Bargalló; L. A. Spalletti; P. Enrique; I. Queralt (Journal of Iberian Geology, 2019)

In Situ Tissue Labeling of Cerebral Amyloid Using HIV-Related Tat Peptide - E. Maderna; L. Colombo; A. Cagnotto; G. Di Fede; A. Indaco; F. Tagliavini; M. Salmona; G. Giaccone (Molecular Neurobiology, 2018)

Beneficial and Safety Properties of a Corynebacterium vitaeruminis Strain Isolated from the Cow Rumen - M. Colombo; N. P. A. Castilho; S. D. Todorov; L. A. Nero (Probiotics and Antimicrobial Proteins, 2017)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - M. J. Bompadre; L. Fernández Bidondo; V. A. Silvani; R. P. Colombo; M. Pérgola; A. G. Pardo; A. M. Godeas (Symbiosis, 2015)

Performance of Bemisia tabaci (Genn.) Biotype B (Hemiptera: Aleyrodidae) on Weeds - L D M Sottoriva; A L Lourenção; C A Colombo (Neotropical Entomology, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Trends in Surface Water Chemistry in Acidified Areas in Europe and North America from 1990 to 2008 - Øyvind A. Garmo; Brit Lisa Skjelkvåle; Heleen A. de Wit; Luca Colombo; Chris Curtis; Jens Fölster; Andreas Hoffmann; Jakub Hruška; Tore Høgåsen; Dean S. Jeffries; W. Bill Keller; Pavel Krám; et al. (Water, Air, & Soil Pollution, 2014)

Apple ( Malus domestica L. Borkh) as an emerging model for fruit development - G. Eccher; S. Ferrero; F. Populin; L. Colombo; A. Botton (Plant Biosystems, 2014)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

Molecular Identification of Melanised Non-Sporulating Moulds: A Useful Tool for Studying the Epidemiology of Phaeohyphomycosis - Daniel W. C. L. Santos; Ana Carolina B. Padovan; Analy S. A. Melo; Sarah S. Gonçalves; Viviane R. Azevedo; Marilia M. Ogawa; Tainá Veras Sandes Freitas; Arnaldo L. Colombo (Mycopathologia, 2013)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Detection of Helicobacter pylori, Enterococcus faecalis, and Pseudomonas aeruginosa in the subgingival biofilm of HIV-infected subjects undergoing HAART with chronic periodontitis - L. Souza Gonçalves; R. Souto; A. P. V. Colombo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Systematic GIS-based landslide inventory as the first step for effective landslide-hazard management - A. Colombo; L. Lanteri; M. Ramasco; C. Troisi (Landslides, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Successful Treatment of an Aspergillus Brain Abscess with Caspofungin: Case Report of a Diabetic Patient Intolerant of Amphotericin B - A. L. Colombo; R. C. Rosas (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Acute Toxicity of Organophosphorus Insecticides to Marine Invertebrates - L. Guzzella; A. Gronda; L. Colombo (Bulletin of Environmental Contamination and Toxicology, 1997)